Multiculturalism in Korean Way: the Difficulties of the Alternative Mass Media in South Korea - A, Yem N; A, Pokhlebayeva N. (Farabi Journal of Social Sciences, 2019)
Abstract. Labor migration along with the new phenomenon in Korea such as marital migration found out weak sides of politics in the «New Korea».In research, attention is payed to selective policy of multiculturalism in the country. The governmental mass media as a basic instrument in forming the public opinion build the stereotypes in relation to the migrants in frames of such a policy. In turn the experience of the aspect the experience of the appearance of the alternative mass media «migrants for migrants» shows «deficiencies» in the existent paradigm about the social nature of migrants in South Korea. The limitations in the considered material gives the new directions for the following research of migrants in whole and marital migrants in particular. The South Korea deserves special attention to discussion of the multiculturalism because it is considered as the most ethnically homogeneous country in the world. In spite of the Korean Mass Media, governmental channels release many programs the basic character of which is the stereotype of the compassion and pity to migrant workers .That causes the displeasure and the desire to show migrant workers as members of the Korean society who invest huge contribution to Korea. The author considers that Mass Media created by the migrant workers is instrument that connects the Korean society and migrant workers. The limitations in considered materials gives new directions for the further research of migrants as a whole and marital migrants as a part of this formation.